A CRITICAL DISCOURSE ANALYSIS OF BIG BROTHER WATCH’S STOP COVID PASSES CAMPAIGN - Bachtiar, Iman Yusuf; Handayani, Lucia Lusi Ani (International Review of Humanities Studies, 2023)
Nineteen Eighty-Four has been widely recontextualised in many different situations, but there has not been any discourse that tries to relate it with surveillance issues in the U.K. in the context of Covid-19 pandemic other than Big Brother Watch’s Stop Covid Passes campaign. This paper aims to discuss how the civil liberties organisation brings the fear of surveillance state presented in the novel into the real life situation happening in the U.K. society.via their public campaign called Stop Covid Passes. The campaign showcases a lot of negative evaluation of the mandatory Covid passes. However, not all agree with the campaign, and many have criticised it as an anti-vaccine movement. This paper conducts qualitative research through the three-dimensional framework of Critical Discourse Analysis (CDA) presented by Norman Fairclough to reveal the organisation's true intention behind the campaign and to examine the role of Nineteen Eighty-Four in this particular context. The findings show that the intention is indeed to stop the U.K. from becoming a surveillance state.